2012
DOI: 10.1038/bjc.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of a cell cycle progression signature for prostate cancer death in a conservatively managed needle biopsy cohort

Abstract: Background:The natural history of prostate cancer is highly variable and it is difficult to predict. We showed previously that a cell cycle progression (CCP) score was a robust predictor of outcome in a conservatively managed cohort diagnosed by transurethral resection of the prostate. A greater need is to predict outcome in patients diagnosed by needle biopsy.Methods:Total RNA was extracted from paraffin specimens. A CCP score was calculated from expression levels of 31 genes. Clinical variables consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
260
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(283 citation statements)
references
References 15 publications
6
260
2
9
Order By: Relevance
“…Although multiple prior studies have related genomic markers to PCa clinical outcomes [17][18][19][20]51], the development of GPS specifically addresses the impact of tumor sampling in predicting aggressive PCa and included central pathology review and a large number of clinical recurrence events providing robust statistical power. By adding independent molecular information to established risk parameters, the GPS improves risk stratification at time of diagnosis and may favorably shift the balance of risks and benefits for men who are candidates for AS and facing challenging decisions regarding optimal management of localized PCa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiple prior studies have related genomic markers to PCa clinical outcomes [17][18][19][20]51], the development of GPS specifically addresses the impact of tumor sampling in predicting aggressive PCa and included central pathology review and a large number of clinical recurrence events providing robust statistical power. By adding independent molecular information to established risk parameters, the GPS improves risk stratification at time of diagnosis and may favorably shift the balance of risks and benefits for men who are candidates for AS and facing challenging decisions regarding optimal management of localized PCa.…”
Section: Resultsmentioning
confidence: 99%
“…Although many groups have demonstrated the potential of gene expression analysis to predict outcome in localized PCa [17][18][19][20], frequent genetic differences between regions of individual tumors and limited tumor sampling by needle biopsy pose challenges to molecular-based assays in PCa [21,22]. With these challenges in mind, we conducted two studies to identify genes for which expression in both prostatectomy and biopsy tissues consistently correlates with tumor aggressiveness regardless of multifocality, heterogeneity, or technical challenges associated with limited tumor obtained through biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…CCP scores were retrospectively assessed for 349 men conservatively managed within the Transatlantic Prostate Group. 71 Ten-year rates of prostate cancer death associated with CCP score groups <0, 0-1, 1-2, 2-3, and >3 were 19.3%, 19.8%, 21.1%, 48.2%, and 74.9%, respectively. In multivariable analysis, the CCP score (HR for one-unit change: 1.65; 95% CI, 1.31-2.09), Gleason score >7 (HR 1.90; 95% CI, 1.18-3.07), and PSA (HR 1.37; 95% CI, 1.05-1.79) significantly predicted prostate cancer death.…”
Section: Molecular Testing In Active Surveillancementioning
confidence: 91%
“…A recent study reported that the measurement of the expression level of 31 genes involved with CCP from biopsy tissue provides the strongest independent predictor of cancer death outcome yet described ( Figure 1). 8 …”
Section: Cell Cycle Progression Markersmentioning
confidence: 99%